2015 IEEE 19th International Conference on Computer Supported Cooperative Work in Design (CSCWD) 2015
DOI: 10.1109/cscwd.2015.7231032
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud collaborative approach for managing patients wellness

Abstract: Patients with chronic diseases or people with special health care needs are typically monitored by various health experts that address the problem from several perspectives. These experts usually do not interact directly between them; therefore, the instructions given to the patient by one of them are provided disregarding advices and instructions provided by the others. The collaboration between different health experts in a real context is mandatory to ensure the proper monitoring of the patient. This kind o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has been reported that remote monitoring of personal wellbeing, through vital signs together with existing data, could significantly improve disease prevention, management, and rehabilitation [70], [71]. Ruiz-Zafra et al [72] investigated the effectiveness of a centralized (cloud-based) health platform for integrating advice from different health experts on collaborative management and monitoring of different types of patients.…”
Section: B Sensor-based Monitoring Of Personal Healthmentioning
confidence: 99%
“…It has been reported that remote monitoring of personal wellbeing, through vital signs together with existing data, could significantly improve disease prevention, management, and rehabilitation [70], [71]. Ruiz-Zafra et al [72] investigated the effectiveness of a centralized (cloud-based) health platform for integrating advice from different health experts on collaborative management and monitoring of different types of patients.…”
Section: B Sensor-based Monitoring Of Personal Healthmentioning
confidence: 99%